Family Hope Program Strategy in Improving the Welfare of the Mandalling Natal Community (Case Study: Social Service Mandalling Natal) - Maisaroh Maisaroh; Maryam Batubara (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
Education is the process of influencing learnes to adapt to the environment and can bring about changes in borth within and within the community. However, the scarcity of economics precludes schooling and even dropouts because they help families make ends meet. The study aims to know the implementation of policies and obstacles in the hope family program The study employs qualitative methods in which it is descriptive that give a clear picture of the problem at hand. Data collection techniques through interviews to informants who know information about the implementation of PKH policy, literature studies, observation, and documentation to support the results of the interview. The study shows tha the implementation of executive policy PKH has been seen from the few factors which are standard and target policy, human reseources and money reseources, executive agent PKH characteristics assist the recipient well, executive organization communication is well established, the social, economic, and political environment supports PKH. The study is based on the fact that the economic growth in the country will be affected mainly by education, with the existence of so- called debtors, it is possible to send their children to school even if there is a problem.